A case series of adult abdominoscrotal hydrocele: A rare condition (Asian Journal of Medical Sciences, 2024)
Abdominoscrotal hydrocele (ASH) is a relatively rare variant of hydrocele in both adult and pediatric populations. The incidence among adults is